THE STUDY OF VOCABULARY SIZE OF SENIOR HIGH SCHOOL STUDENTS WHO PARTICIPATED IN ENGLISH DEBATE COMPETITION - Cahya, Eka Sulistia (Universitas Halu Oleo, 2019)
This study was conducted to know whether there is any significant difference in vocabulary size between students who participated and those who did not participate in English debate competition. This study applied ex post facto design. The sample of this research was 30 students from 3 different schools, they were SMAN 2 Kendari, SMAN 4 Kendari, and SMAN 5 Kendari. The students were divided into two Â groups Â consist Â ofÂ 15 Â students. Â The Â researcher Â used Â the Â test Â of New Vocabulary Level Test (NVLT) to collect the data and the data were analyzed byÂ using Â SPSS Â 16.0. Â The Â result Â showed Â that Â there Â is Â a Â significant difference of the mean score of the total correct answer that students could answer which automatically affect their amount of vocabulary size. The mean score of group 1 is 104 correct answer and it is higher than group 2 which gets the mean score of the correct answer only 82. The significant value of sig(2-tailed) is 0.001, it is lower than 0.05 (sig (2-tailed) < âˆ). It can be concluded that the alternative hypothesis (H1) is accepted and indicated there is a significant difference in vocabulary size between students who participated in English debate competition andÂ Â thoseÂ Â whoÂ Â didÂ Â notÂ Â participate,Â Â whileÂ Â theÂ Â nullÂ Â hypothesisÂ Â (H0)Â Â was automatically rejected.Â Keywords : Debate Competition, Vocabulary Size